Culture-Related Health Disparities in Quality of Life: Assessment of Instrument Dimensions Among Chinese - Li, Minghui; Bao, Zhang; Lv, Gang; Zhou, Jianying; Chen, Pingyu; Luo, Nan (Frontiers in Public Health, 2021)
Background: Health-related quality of life (HRQoL) is one of the major focuses of primary care. However, HRQoL instruments used in China are mainly developed from Western countries. Such instruments may not cover all important health concepts valued by the Chinese as health is a culture-specific concept. Objectives: The objectives of this study are to identify culture-specific health dimensions and culture-related health disparities in primary care that are considered important by Chinese living in China. Methods: A purposive sample of 164 adult Chinese (67 healthy persons and 97 patients) were interviewed face to face. In-depth open-ended questions were asked to elicit culture-specific dimensions of quality of life in primary care settings in China. Results: Twelve health dimensions were identified. Five most frequently mentioned dimensions were: mood (N=52, 31.71%), physical activities (N=48, 29.27%), work (N=40, 24.39%), diet (N=32, 19.51%), and vitality (N=28, 17.07%). Significantly more healthy persons reported mood (49.25% vs. 19.59%, P<.001), mindset (16.42% vs. 0.00%, P<.001), and self-care (11.94% vs. 2.06%, P=.016) characterizing good HRQoL, while more patients emphasized on work (4.48% vs. 38.14%, P<.001). Diet and vitality appeared to be culture-specific dimensions related to health among Chinese. Conclusions: To better adapt or develop HRQoL instruments for Chinese, dimensions or items regarding diet should be included and disparities in the meaning of vitality between Chinese and Western cultures should be considered.